1964
DOI: 10.1104/pp.39.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Chloroplast Development in Euglena. V. Pigment Biosynthesis, Photosynthetic Oxygen Evolution and Carbon Dioxide Fixation during Chloroplast Development

Abstract: Our studlies wvith Euglena (2, 6, 14, 19, 20) have suggestedl that dark-grown cells containi approximately 30 proplastids whiclh develop into about 10 chloroplasts xvhen the cells are exposed to light. The existence of these proplastids, originally inferred from studlies on ultraviolet inactivation ain(l photoreactivation of chloroplast formiiation (14, 19). was confirimie(I by fluorescence ani(I electron miiicroscopy (2, 6). Other workers have stu(lie(l some of the initial steps invTolved wvhen dlark-groxvn c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 168 publications
(76 citation statements)
references
References 22 publications
4
72
0
Order By: Relevance
“…Cur0 teno id forination When normal dark-grown resting organisms were exposed to light, carotenoid levels did not change significantly during the first 1 2 to 14 h of development (Stern et al 1964b). The initial carotenoid levels were the same in streptomycin treated and untreated organisms up to this time but further carotenoid accumulation was inhibited ( Table I ) .…”
Section: J G B O V a R N I C K A N D O T H E R S R E S U L T S A N mentioning
confidence: 73%
See 4 more Smart Citations
“…Cur0 teno id forination When normal dark-grown resting organisms were exposed to light, carotenoid levels did not change significantly during the first 1 2 to 14 h of development (Stern et al 1964b). The initial carotenoid levels were the same in streptomycin treated and untreated organisms up to this time but further carotenoid accumulation was inhibited ( Table I ) .…”
Section: J G B O V a R N I C K A N D O T H E R S R E S U L T S A N mentioning
confidence: 73%
“…The development of photosynthetic CO,.fixation in the presence of strcpfotnycin Stern et al (1964b) have described the normal appearance of photosynthetic competence during chloroplast development in Euglena and have shown that net photosynthetic carbon dioxide fixation can be detected by 6 h development, with net oxygen evolution detectable at about 3 to 4 h development (Schiff, 1963). As with chlorophyll, photosynthetic capacity as measured by CO, fixation increased slowly for nearly 1 2 h, after which the increase became much more rapid.…”
Section: Grcwi-coloiiy Fortizing Abilit)' Of Notdividing Organisinsmentioning
confidence: 99%
See 3 more Smart Citations